Teori Psikologi Manajemen dalam Lembaga Pendidikan: Kajian Literature Review Sistematis tentang Pengaruh Faktor Psikologis terhadap Kinerja Pendidik dan Mutu Pendidikan - Rifkiatul Musarofah; Dina Talitha Salsabila; St. Nur Azizah; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Management psychology plays a crucial role in enhancing the effectiveness of educational organizational management, particularly in understanding individual behavior, work motivation, leadership, and communication within the educational environment. The dynamic development of educational institutions requires a managerial approach that focuses not only on administrative aspects but also on the psychological aspects of the human resources involved. Therefore, the study of management psychology in education is essential to understand how this approach can support improvements in educational quality. This study aims to review and synthesize various studies on the application of management psychology in educational contexts and identify emerging research trends. The research questions posed are: (1) What are the trends and focuses of research on management psychology in education? and (2) What is the role of management psychology in improving the effectiveness of educational institution management? This study is expected to provide insights into how management psychology can be applied to enhance managerial performance and quality in education.